COMPUTATIONAL STUDIES OF L-2-HALOACID DEHALOGENASE GENE FROM PSEUDOMONAS PUTIDA KT2440 - Kelvin, Bernardus
Dehalogenase is a class of hydrolases that has important roles in degrading varies of xenobiotic organohalides in nature. One of the subclass of dehalogenases is haloacid dehalogenase, a type of dehalogenase that remove halogen atom in haloalkanoic acid. A brief study on broad variety of bacteria proves that most of soil bacteria belong to Pseudomonas genus owns haloacid dehalogenase gene. This research was focused on finding the gene encoding haloacid dehalogenase from Pseudomonas putida KT2440. Pseudomonas putida KT2440 is a Gram-negative bacterium that has no TOL plasmid. This strain is certified to be released to the environment by the Recombinant DNA Advisory Committee. In this research, genomic study was done using the database from NCBI. Analysis were performed using various softwares including GROMACS, VMD, R Studio, Python 3, and online-based-server service like Zhang-server. Haloacid dehalogenase gene screening in Pseudomonas putida KT2440 genome was done by using NCBI CD-Blast utilizing similar haloacid dehalogenase pattern known in 8 bacteria, resulting in 5 genes that encodes protain that has similar motif to L-2-haloacid dehalogenase. A 3D protein structure was modelled to these 5 haloacid dehalogenases putative genes using Zhang-server. A comparative study of similarities within these putative genes with L-2-haloacid dehalogenase shows only 3 putative proteins with decent structural similarities. Further study using active site comparison indicated only 2 proteins with close similarities. Further proofs were performed by molecular docking and molecular dynamics to see the binding affinity between these two putative proteins and substrates: L-2-chloropropanoic acid, D-2-chloropropanoic acid, and 3-chloropropanoic acid, with 2-chorloetanoic acid as positive control and chloropyrifos as negative control. The studies suggested that Pseudomonas putida KT2440 encodes only 1 haloacid dehalogenase gene.